Developing a Minimal Pairs’ Package for Persian-speaking Children: A Preliminary Study - Hananeh Ardalan; Talieh Zarifian; Akram Ahmadi; Mona Ebarahimipour (Iranian Rehabilitation Journal, 2020)
Objectives: Different treatment approaches have been introduced for children with Speech Sound Disorders (SSD). Minimal pair intervention, Metaphon therapy, and parents and children together approach as linguistically-based approaches are routinely utilized in this population and both of them shared minimal pairs as a common component. The purpose of the current study was to develop and investigate the validity of the material for this treatment approach for Persian-speaking children. Methods: To develop the minimal pairs’ package, 10 phonological processes were selected based on the literature. Several minimal pairs were generated for each phonological process and their content validity was determined by the content validity ratio. In the next step, the appropriate pictures were selected. In the final step, the package was administrated to 45 monolingual Persian-speaking children. Results: Based on the experts’ opinions, 293 minimal pairs out of 303 pairs, obtained appropriate content validity values (content validity ratio >0.62) and 10 minimal pairs were excluded at this step. Finally, 256 minimal pairs remained after the administration of the package on the subjects. Discussion: Based on the results of the current project, it seems that the Persian photo minimal pairs’ package is a valid material for use in related speech treatment in children with SSD.